Report of a Working Group on Allium: Sixth meeting, 23-25 October 1997, Plodiv, Bulgaria - Maggioni, L.; Astley, D.; Rabinowitch, H.; Keller, J.; Lipman, E.; European Cooperative Programme for Plant Genetic Resources (1999)
The 6th meeting of the Allium working group provides information on national collections, research activities and regeneration activites related to Allium genetic resources in Europe.